The effect of classical foot massage on insomnia and anxiety in preeclamptic pregnant women: a randomized controlled study - Kirca, Ayca Solt; Cetin, Nurdilan Sener (Assoc Medica Brasileira, 2024)
OBJECTIVE: Preeclampsia is one of the most common complaints during pregnancy. Preeclamptic pregnant women may experience insomnia and anxiety. METHODS: This study was a randomized controlled trial with 71 preeclamptic women. In the experimental group, a foot massage was done for 3 days in a week. In the control group, any applications were not done. These groups were assessed for insomnia and anxiety levels. RESULTS: In this study, it was found that classical foot massage significantly reduced (12.45 +/- 5.74 vs. 33.4 +/- 6.41) insomnia and anxiety compared with the control group (18.8 +/- 6.44 vs. 39.19 +/- 8.31, respectively, p<0.05). CONCLUSION: The classical foot massage can effectively decrease insomnia and anxiety symptoms.
Keywords: Massage; Insomnia; Anxiety; Pregnant women